Scalable and Efficient Spatial-Aware Parallelization Strategies for Multimedia Retrieval - Andrade, Guilherme; Teodoro, George; Ferreira, Renato (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2020)
Similarity search is a key operation in several multimedia applications, including online Content-Based Multimedia Retrieval (CBMR) services. These applications have to deal with very large databases and are submitted to high query rates. In this context, scalability in distributed memory system is critical to assemble the required computing power and memory space. However, we have identified that the Data Equal Split (DES) parallelization and associated data partition strategy employed by the related works on the domain have limitations in terms of efficiency and scalability. Therefore, in this paper, we developed and implemented a framework for similarity search execution on distributed memory machines and proposed a novel class of data partition strategies that takes into account the data spatial organization in its distribution. This approach leads to a reduction in communication traffic and in costs associated with processing each task in local searches carried out in the distributed machine. Our approach attained a speedup of 2.4× on top of DES in the baseline case (5 nodes) and also achieves higher scalability efficiency and is 14.5× faster when 160 nodes are used. In fact, our novel data organization led to superlinear scalability in all configurations evaluated.